UNDERSTANDING THE PROCESS OF CAREGIVING FOR MOTHERS BY DAUGHTERS: A VIEW OF THE PARENT-CHILD RELATIONSHIP - Baba, A (Innov Aging, 2018)
OBJECTIVE: Nowadays, daughters, as opposed to daughters-in-laws, are expected to take the role of caregiver in Japan. However, this may sometimes cause mental strain to the caregivers as the children who were initially cared for are now expected to take care of their parents. A peculiar, intimate, and distorted mother-daughter relationship can further aggravate this situation. But, there are not enough studies on the process of acceptance of losing their mother-images and caregiving for their elderly mothers. This study aimed to explore how daughters could understand providing care to their mothers for a long-term mother-daughter relationship. METHOD: Semi-structured interviews were conducted with 15 daughters who were caring or had cared for their mothers at home. Participants were asked about caregiving and the relationships with their mothers. Data were analyzed based on the Grounded Theory focusing on the mental process. RESULT: Four patterns of understanding the caregiving process were found: Natural acceptance; resignation; detachment; and conflict. These processes were influenced by seven factors: Perception of caregiving as a usual role; understanding ageing and caregiving; focusing on residual functions; enjoying communication with the mothers (even with dementia); having conventional mothers; weakened self-images; and positive feedback from the mothers. CONCLUSION: Four patterns of the process in which the daughters understood caregiving for their elderly mothers and seven relevant factors were revealed. With regards to these process patterns and factors, mental support should be provided to the caregivers to enable them to live their lives without serious mental strains.